Effect of Essential Service Quality on Officers' Satisfaction and Morale in Navy Town, Lagos - Maiyaki, Sani Audu; Ishiyaku, Bala; Yunusa, Muhammed Hayatu; Ibrahim, Aisha; Milala, Sani Inusa (Journal of Social Transformation and Regional Development, 2022)
The study aims to evaluate the effect of essential service quality on Junior Non-Commissioned Officers' satisfaction and morale in Navy Town, Lagos, to suggest measures of improvement. The study covers junior non-commissioned officers Quarters of Navy Town, Lagos. A quantitative method was adopted for this study. The population size in this study comprises about 1,000 apartments and the sample size is 400. The respondents were selected by the systematic sample method. The study employed a questionnaire as an instrument for the data collection. Data collected were analysed using descriptive statistics (mean and standard deviation). A total number of 372 questionnaires were retrieved from the respondents and 365 were used in the analyses after data screening. Bureaucracy and under-costing mostly influence the quality of essential service, with a delivery method such as contract contributing less. It is also recommended that Barrack Maintenance Unit (BMU) as well as the Nigerian Naval Headquarters should incorporate policies that would encourage the efficient use of services provided as it will help to increase the life span of the facilities. The barrack maintenance and services provided be carried out through direct labour to ensure effectiveness. The above recommendations are hopefully expected to reverse the current trend of junior non-commissioned officers' satisfaction, consequently improve to better sustainable improvement on barrack accommodation and facilities.